Hadith #508 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Sulaiman bin Musa al-Ashdaq سليمان بن موسى الأموي الأشدق; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to pray ‘Asr, then a person could go to Quba’.” One of them said: “And he would come to them when they were prayed.” The other said: “And the sub was still high.” Both Az-Zuhri and Ishaq bin ‘Abdullah narrated it from Anas, so the reference is about them.
Grade:

Hadith #983 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Abu Hurairah; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan al-Nasa'i)
“We entered upon Anas bin Malik and he said: ‘Have you prayed?’ We said: ‘Yes.’ He asid: ‘O slave girl, bring me water for Wudhu! I have never prayed behind any Imam whose prayer more closely resembles the prayer of the Messenger of Allah (ﷺ) than this Imam of yours.'” Zaid said: “Umar bin Abdul Aziz used to complete the bowing and prostration (without rushing) and lighten the standing and sitting.”
Grade:

Hadith #1338 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Aisha bint Abi Bakr; Asim al-Ahwal عاصم الأحول; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Ibrahim bin Sdran محمد بن إبراهيم بن صدران; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) commanded me to recite Al-Mu’awwidhat following every prayer.”
Grade:

Hadith #2162 - Sunan al-Nasa'i - Abdul Hameed bin Dinar al-Ziyadi عبد الحميد بن دينار صاحب الزيادي; Abdullah ibn al-Harith ibn Nawfal; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah and Zaid bin Thabit had Sahur, then they went and started to pray Subh.” We said to Anas: “How long was there between their finishing and their starting to pray?” He said: “As long as it takes a man to recite fifty Verses.”
Grade:

Hadith #2193 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ishaq bin Rahwaya إسحاق بن راهويه; Urwa ibn al-Zubayr عروة بن الزبير; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan al-Nasa'i)
“We were with ‘Ammar and a roast sheep was brought and he said: ‘Eat.’ One of the people turned away and said: ‘I am fasting ‘Ammar said: Whoever fasts on the day concerning which there is doubt, has disobeyed Abu Al-Qasim.”‘ ‘
Grade:

Hadith #2211 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-'Ala' bin Hilal bin 'Umar bin Hilal العلاء بن هلال بن عمر بن هلال; Ali ibn Abi Talib; Hilal bin al-'Ala' bin Hilal bin 'Umar هلال بن العلاء بن هلال بن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Zayd ibn Harithah (Sunan al-Nasa'i)
“Abu Hurairah told me that the Messenger of Allah said: ‘Whoever spends the nights of Ramadan in prayer (Qiyam) out of faith and in the hope of reward, he will be forgiven his previous sins, and whoever spends the night of Lailat Al-Qadr in prayer out of faith and in the hope of reward, he will be forgiven his previous sins.”‘
Grade:

Hadith #3308 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Ayoub al-Sakhtiyani أيوب السختياني; Muhammad bin Swa'a محمد بن سواء; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Sunan al-Nasa'i)
“What becomes unlawful (for marriage) through breast-feeding is that which becomes unlawful through lineage.”
Grade:

Hadith #4165 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Abdullah ibn al-Harith ibn Nawfal; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“You have to obey when you feel energetic and when you feel tired, during your ease and your hardship, and when others are preferred over you.”
Grade:

Hadith #4457 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Hakim ibn Hizam; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
from his father, form his grandfather – the on the Day of Kahaibar, the Messenger of Allah forbade the flesh of domesticated donkeys and of al-Jallalah (animals that eat dung), and (he forbade) riding them and eating their mat.”
Grade:

Hadith #4464 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘There will come a time when a man will not care where his wealth comes from, whether (the source is) Halal or Haram.”
Grade:

Hadith #4488 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Abu Hurairah; Da'ud bin Qays al-Fra'a داود بن قيس الفراء الدباغ; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد (Sunan al-Nasa'i)
“When two people meet to engage in trade the transaction between them is not binding until they separate, unless they have chosen to conclude the transaction.”
Grade:

Hadith #5458 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Ahmed bin Suliaman أحمد بن سليمان; Asim al-Ahwal عاصم الأحول; Mhadr Bdad Ma'jmh محاضر بضاد معجمة; Zayd bin Arqam (Sunan al-Nasa'i)
“The Messenger of Allah had supplications that he never omitted to recite. He used to say: ‘Allahumma inni a’udhu bika minal-hammi, wal-hazani, wal-‘ajzi, wal-kasali, wal-bukhli, wal-jubni, wa ghalabatar-rijal (O Allah, I seek refuge with You from worry, grief, incapacity, laziness, miserliness, cowardice and being overpowered by (other) men.)”
Grade:

Hadith #5538 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Asim al-Ahwal عاصم الأحول; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan al-Nasa'i)
“I heard the Messenger of Allah say: ‘Allahumma, inni a’udhu bi-‘azamatika an ughtala min tahti (O Allah, I seek refuge in Your greatness from being swallowed up from beneath me.)'”
Grade:

Hadith #2455 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Umm Hani bint Abi Talib; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
When the Prophet (ﷺ) entered upon me, he would ask: Do you have food ? When we said: No, he would say: I am fasting. Waki’ added in his version: Another day when he entered upon us, we said: Messenger of Allah, some pudding (hair) has been presented to us and we have retained it for you. He said: Bring it to me. Talhah said: He fasted in the morning, but broke his fast (that day).
Grade: Sahih

Hadith #3458 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
When Abu Zur’ah made a business transaction with a man, he gave him the right of option. He then would tell him: Give me the right of option (to annul the bargain). He said: I heard AbuHurayrah say: The Messenger of Allah (ﷺ) said: Two people must separate only by mutual consent.
Grade: Hasan Sahih

Hadith #4287 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Umm Salamah (Sunan Abi Dawud)
The other narrators mentioned “nine years” from Hisham except Mu’adh.
Grade: Da'if

Hadith #298 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; Ahmed bin Manay' أحمد بن منيع; Aisha bint Abi Bakr; Asim al-Ahwal عاصم الأحول; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Jami' al-Tirmidhi)
“When Allah’s Messenger said the Salam he would not remain seated except long enough to say: (Allahumma antas-salam, wa minkas-salam, tabarakta dhal jalali wal-Ikram) ‘O Allah! You are the One free of defects, and perfection is from You. Blessed are You, Possessor of Majesty and Honor.'”
Grade:

Hadith #1242 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “Animals are not proper on credit, and there is no harm in a hand to hand (exchange).” The Hadith is Hasan Sahih.
Grade:

Hadith #1685 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; ibn Mas'ud; Khlf bin Khlyfh خلف بن خليفة (Jami' al-Tirmidhi)
“The Prophet (ﷺ) rode a horse belonging to Abu Talhah called Mandub. He said: ‘There is nothing to be frightened of, and we found him to be (quick) like the sea.'” There is something on this topic from Ibn ‘Amr Al-‘As.
Grade:

Hadith #1783 - Jami' al-Tirmidhi - Abdul Karim bin Abi al-Mukharaq عبد الكريم بن أبي المخارق; Abdullah ibn al-Harith ibn Nawfal; Ahmed bin Manay' أحمد بن منيع; Sufyan bin 'Uyaynah سفيان بن عيينة (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) prohibited that a man should put on sandals while he is standing.” This Hadith is Gharib. Muhammad bin Isma’il said: “This Hadith is not correct, not the Hadith of Ma’mar from ‘Ammar bin Abi ‘Ammar, from Abu Hurairah (no.1775).”
Grade:

Hadith #2127 - Jami' al-Tirmidhi - Abdah bin 'Abdullah al-Saffar عبدة بن عبد الله الصفار; Abdullah ibn al-Harith ibn Nawfal; Anas ibn Malik; Asim al-Ahwal عاصم الأحول; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Jami' al-Tirmidhi)
“that a man from ” He said: ‘Yes.” He said: “Then what are their colors?” He said: “Red.” He said: “Is there a gray one among them?” He said: “Yes, there is a grey one among them.” He said: “From where does that come?” He said: “Perhaps it is hereditary.” He said: “Then in the same way, perhaps it is his heredity.” This Hadith is Hasan Sahih.
Grade:

Hadith #3872 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; al-'Abbas ibn 'Abd al-Muttalib; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Yazid bin Abi Ziyad يزيد بن أبي زياد; Yusuf bin Musa bin Rashid al-Qatan يوسف بن موسى بن راشد القطان (Jami' al-Tirmidhi)
that ‘Ali mentioned the daughter of Abu Jahl (for marriage), and that reached the Prophet (ﷺ) so he said: “Indeed Fatimah is but a part of me, I am harmed by what harms her and I am uncomfortable by what makes her uncomfortable.”
Grade:

Hadith #3873 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; al-Mtlb bin Abi Wda'h; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) said to ‘Ali, Fatimah, Al-Hasan and Al-Husain: “I am at war with whoever makes war with you, and peace for whoever makes peace with you.”
Grade:

Hadith #3876 - Jami' al-Tirmidhi - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abdullah ibn al-Harith ibn Nawfal; Abu Hurairah; al-Minhal bin 'Amr al-Asadi المنهال بن عمرو الأسدي مولاهم الكوفي (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) called Fatimah on the Day of the Conquest (of Makkah) and he spoke to her, so she cried. Then he spoke to her and she laughed. She said: “So when the Messenger of Allah (ﷺ) died, I asked her about her crying and laughing. She said: “The Messenger of Allah (ﷺ) told me that he will die, so I cried, then he told me that I was the master over all the women of the inhabitants of Paradise, except for Mariam the daughter of ‘Imran, so I laughed.”
Grade:

Hadith #977 - Sunan Ibn Majah - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Asim al-Ahwal عاصم الأحول; Ibn Abi al-Shuwarab محمد بن عبد الملك بن أبي الشوارب; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan Ibn Majah)
It was narrated from Anas bin Malik that the Messenger of Allah (ﷺ) used to recite Qunut in the Subh prayer, and he used to supplicate in it against one of the Arab tribes for a month, then he stopped doing so.
Grade:

Hadith #992 - Sunan Ibn Majah - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; Abdullah ibn al-Harith ibn Nawfal; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Asim al-Ahwal عاصم الأحول (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said concerning the fear prayer: “The Imam should lead one group in prayer, and they should perform one prostration, and there should be another group between them and the enemy (guarding them). Then those who did the prostration with their leader should move away, and take the place of those who have not yet prayed. Then those who have not yet prayed should come forward and perform one prostration with their leader. Then their leader should move away, and his p
Grade:

Hadith #1214 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) saw some people riding on their animals in a funeral (procession). He said: ‘Do you not feel ashamed that the angels of Allah are walking on foot and you are riding?’”
Grade:

Hadith #1386 - Sunan Ibn Majah - Abd Rabba bin Sa'id bin Qays bin 'Amr عبد ربه بن سعيد بن قيس; Abdullah bin Naf' عبد الله بن نافع بن العمياء; Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Mtlb bin Abi Wda'h; Shababa bin Sawar شبابة بن سوار الفزاري; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“A Bedouin came to the Prophet (ﷺ) and said: ‘I have seen the new crescent tonight.’ He said: ‘Do you bear witness that none has the right to be worshipped but Allah and that Muhammad is the Messenger of Allah (ﷺ)?’ He said: ‘Yes.’ He said: ‘Get up, O Bilal, and announce to the people that they should fast tomorrow.’” Abu ‘Ali said: “This is how it was narrated from Walid bin Abu Thawr and Hasan bin ‘Ali. It was also narrated from Hammad bin Salamah, but he did not
Grade:

Hadith #1442 - Sunan Ibn Majah - Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Sufyan bin 'Uyaynah سفيان بن عيينة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“Whoever fasts three days in every month, that is fasting for a lifetime.” Then, in testimony of that, Allah revealed: “Whoever brings a good deed shall have ten time the like thereof to his credit.” So one day is equivalent to ten (in reward).
Grade:

Hadith #2016 - Sunan Ibn Majah - Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Sunan Ibn Majah)
“Abdullah bin Shaddad and Abu Barzah had a dispute about paying in advance. They sent me to ‘Abdullah bin Abu Awfa to ask him about it. He said: ‘We used to make payments in advance at the time of the Messenger of Allah (ﷺ) and the time of Abu Bakr and ‘Umar, for wheat, barley, raisins and dates, to people who did not yet possess those things.’ I asked Ibn Abza, and he said something similar.”
Grade:

Hadith #3208 - Sunan Ibn Majah - Abdul al-Kareem bin Malik عبد الكريم بن مالك الجزري أبو سعيد; Abdullah ibn al-Harith ibn Nawfal; Ali ibn Abi Talib; ibn Abbas; Muhammad bin Ibrahim bin 'Uthman محمد بن إبراهيم بن عثمان; Uthman bin Muhammad (Sunan Ibn Majah)
The Prophet (ﷺ) said: “Cool it down with water,” and he said: “It is from the heat of Hell-fire.”
Grade:

Hadith #3743 - Sunan Ibn Majah - Abdullah ibn al-Harith ibn Nawfal; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“No one of you should belittle himself.” They said: “O Messenger of Allah, how could anyone of us belittle himself?” He said: “If he sees something concerning which he should speak out for the sake of Allah but does not say anything. Allah will say to him on the Day of Resurrection: “What prevented you from speaking concerning such and such?” He will say: “Fear of the people.” (Allah) will say: “Rather you should have feared Me.”
Grade: